2006
DOI: 10.1021/bi0610101
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of RhoA

Abstract: We have previously shown that redox agents including superoxide anion radical and nitrogen dioxide can react with GXXXXGK(S/T)C motif-containing GTPases (i.e., Rac1, Cdc42, and RhoA) to stimulate guanine nucleotide release. We now show that the reaction of RhoA with redox agents leads to different functional consequences from that of Rac1 and Cdc42 due to the presence of an additional cysteine (GXXXCGK(S/T)C) in the RhoA redox-active motif. While reaction of redox agents with RhoA stimulates guanine nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 57 publications
6
92
0
1
Order By: Relevance
“…42 However, a subset of Rho family GTPases has been observed to be sensitive to oxidants. 43,44 In Rho GTPases, the redox-sensitive motif has been determined to be located directly adjacent to the phosphoryl-binding loop (GXXXXGK[S/T]C) motif. As with Ras, Rho GTPases are sensitive to free radical-mediated oxidation and regulation; however, because the redox-sensitive thiols in Rho GTPases make direct contact with the bound nucleotide, 2-electron oxidation of the phosphoryl-binding loop thiols can also regulate Rho GTPase activity.…”
Section: Nomentioning
confidence: 99%
See 2 more Smart Citations
“…42 However, a subset of Rho family GTPases has been observed to be sensitive to oxidants. 43,44 In Rho GTPases, the redox-sensitive motif has been determined to be located directly adjacent to the phosphoryl-binding loop (GXXXXGK[S/T]C) motif. As with Ras, Rho GTPases are sensitive to free radical-mediated oxidation and regulation; however, because the redox-sensitive thiols in Rho GTPases make direct contact with the bound nucleotide, 2-electron oxidation of the phosphoryl-binding loop thiols can also regulate Rho GTPase activity.…”
Section: Nomentioning
confidence: 99%
“…The seminal papers that first identified the redox-sensitive properties of this motif in the canonical Rho family members (RhoA, Rac1, and Cdc42) showed that exposure to free radical oxidants (nitrogen dioxide and superoxide) resulted in increased nucleotide dissociation, similar to that observed for Ras. 43,44 In these studies, the in vitro-purified GTPases preloaded with [ 3 H]GDP were exposed to various ROS and RNS and monitored for their ability to retain nucleotide binding in the presence of unlabeled GDP. Whereas the non-radical oxidant peroxide stimulated guanine nucleotide dissociation in RhoA, Rac1, and Cdc42 by 10-fold under the conditions tested, the rate of guanine nucleotide dissociation was dramatically enhanced by 500-to 600-fold upon exposure to superoxide, nitrogen dioxide, and hydroxyl radicals.…”
Section: Redox Regulation Of Racmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently identified a distinct redox-sensitive GXXXXGK(S/T)C motif that is conserved in many Rho subfamily proteins such as Rac1, RhoA, RhoC, and Cdc42 (23,24). Notably, the thiol moiety of the Rac1 cysteine (Cys 18 , Rac1 numbering) in the GXXXXGK(S/T)C motif is located at the Rac1 nucleotide-binding site, but the equivalent thiol moiety of the Ras cysteine (Cys 118 , Harvey Ras numbering) in the NKCD motif is remote from the Ras nucleotide-binding site (13).…”
mentioning
confidence: 99%
“…The redox-sensitive Rac1 Cys 18 residue in the GXXXXGK(S/ T)C motif also is likely susceptible to reaction with another cysteine residue of proteins or molecules that contains a thiol moiety to produce protein disulfide. This susceptibility is exemplified by the formation of an intra-protein disulfide of the GXXXXGK(S/T)C motif-containing RhoA (24). Intriguingly, a disulfide cross-link between 6-TGNP and Rac1 is possible.…”
mentioning
confidence: 99%